Placental proteomics provides insights into pathophysiology of pre-eclampsia and predicts possible markers in plasma - Mary, Sheon; Kulkarni, Mahesh J.; Malakar, Dipankar; Joshi, Sadhana Ramchandra; Mehendale, Savita S.; Giri, Ashok P. (Journal of Proteome Research, 2017)
Pre-eclampsia is a hypertensive disorder characterized by the new onset of hypertension >140/90 mmHg and proteinuria after the 20th week of gestation. The disorder is multi-factorial and originates with abnormal placentation. Comparison of the placental proteome of normotensive (n=25) and pre-eclamptic (n=25) patients by gel-free proteomic techniques, identified a total of 2145 proteins in the placenta of which 180 were differentially expressed (>1.3 fold, p<0.05). Gene ontology enrichment analysis of biological process suggested that the differentially expressed proteins belonged to various physiological processes such as angiogenesis, apoptosis, oxidative stress, hypoxia, placental development, which are implicated in the pathophysiology of pre-eclampsia. Some of the differentially expressed proteins were monitored in the plasma by multiple reaction monitoring (MRM) analysis, which showed an increase in Apolipoprotein AI and AII in gestational week 26-30th (2-fold, p<0.01) while haptoglobin and hemopexin decreased in gestational week 26-30th and 40th week/at delivery (1.8 fold, p<0.01) in pre-eclamptic patients. This study provides a proteomic insight into the pathophysiology of pre-eclampsia. Identified candidate proteins can be evaluated further for the development of potential biomarkers associated with pre-eclampsia pathogenesis.